Socorro. Preciso de ajuda
Anexos:
![](https://pt-static.z-dn.net/files/daf/306aff9664e23f864e28a4721ccf54aa.png)
Soluções para a tarefa
Respondido por
1
㏒₄(a-b)=x e a + b = 1/16
㏒₄(a-b) = x => 4ˣ = (a-b)
(a² - b²) = (a+b).(a-b) =>(a² - b²) = 1/16. 4ˣ = 4ˣ /16, então:
㏒₄(a² - b²) = ㏒₄ 4ˣ/16, usando a propriedade de logaritmo de um quociente:
㏒ a/b = ㏒ a - ㏒ b.
㏒₄ 4ˣ/16 = ㏒₄ 4ˣ - ㏒₄ 16 = x.log₄ 4 - log₄ 16 = x.1 - 2 = x - 2
㏒₄(a-b) = x => 4ˣ = (a-b)
(a² - b²) = (a+b).(a-b) =>(a² - b²) = 1/16. 4ˣ = 4ˣ /16, então:
㏒₄(a² - b²) = ㏒₄ 4ˣ/16, usando a propriedade de logaritmo de um quociente:
㏒ a/b = ㏒ a - ㏒ b.
㏒₄ 4ˣ/16 = ㏒₄ 4ˣ - ㏒₄ 16 = x.log₄ 4 - log₄ 16 = x.1 - 2 = x - 2
Perguntas interessantes
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Português,
11 meses atrás
Português,
1 ano atrás
Matemática,
1 ano atrás